2023
DOI: 10.3390/ijms24076142
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Roles of Tumor Necrosis Factor-Alpha (TNF-α) in COVID-19: Prognosis, Therapeutic and Management

Abstract: The coronavirus disease 2019 (COVID-19) became a worldwide concern at the beginning of 2020 and has affected millions. Several previous studies revealed the impact of the imbalanced innate immune response on the progression of COVID-19 and its disease outcomes. High levels of proinflammatory cytokines such as tumor necrosis factor-alpha (TNF-α) and interleukins are produced readily by innate immune cells to fight Severe Acute Respiratory Syndrome-Coronavirus-2 (SARS-CoV-2) infections. Nonetheless, cytokine-med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 96 publications
1
16
0
Order By: Relevance
“…This underpins the importance of immune-modulating anti-cytokine treatments in the clinic for patients with elevated levels of TNF-α and IL-6 in serum to serve better prognosis in inflammatory conditions like sepsis 31 and COVID-19. 32,33,59 Surprisingly, we found that NET release is unaffected when treated with LTB 4 , a significant lipid mediator of inflammation, previously shown to increase neutrophil recruitment and swarming in vivo . 7,60 However, the influence of LTB 4 on NET release, especially in the context of infection, has not been previously explored.…”
Section: Discussionmentioning
confidence: 66%
“…This underpins the importance of immune-modulating anti-cytokine treatments in the clinic for patients with elevated levels of TNF-α and IL-6 in serum to serve better prognosis in inflammatory conditions like sepsis 31 and COVID-19. 32,33,59 Surprisingly, we found that NET release is unaffected when treated with LTB 4 , a significant lipid mediator of inflammation, previously shown to increase neutrophil recruitment and swarming in vivo . 7,60 However, the influence of LTB 4 on NET release, especially in the context of infection, has not been previously explored.…”
Section: Discussionmentioning
confidence: 66%
“…When the body is seriously injured, serum TNF‐α level will be significantly increased. At the same time, the high TNF‐α expression can inhibit the immune function and then increase the risk of further injury 27 . Studies have shown that the TNF‐α level is abnormally high in patients with ovarian cancer 22,28 .…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, the high TNF‐α expression can inhibit the immune function and then increase the risk of further injury. 27 Studies have shown that the TNF‐α level is abnormally high in patients with ovarian cancer. 22 , 28 Here we found that recurrent patients have higher serum TNF‐α level than nonrecurrent patients.…”
Section: Discussionmentioning
confidence: 99%
“…In line with the information reported by Wu et al, we do not observe statistically significant differences in CD147 mRNA levels considering the genotypes of this variant in patients with psoriasis and stable angina [ 24 , 25 ]. Although we did not identify differences in TNF mRNA expression considering the three rs8259T>A genotypes, we know that TNF is a cytokine that mediates inflammation and can cause detrimental tissue damage, that it promotes lung fibrosis, which later results in pneumonia, pulmonary edema, and acute respiratory distress syndrome, that it promotes inflammation and that it is associated with morbidity and mortality in patients with COVID-19 [ 26 ].…”
Section: Discussionmentioning
confidence: 99%